2023
DOI: 10.3390/polym15041049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Fully Biodegradable Composites Based on Poly(butylene succinate) and Biochar

Abstract: Biodegradable polymers offer a promising alternative to the global plastic problems and especially in the last decade, to the microplastics problems. For the first time, samples of poly(butylene succinate) (PBSu) biocomposites containing 1, 2.5, and 5 wt% biochar (BC) were prepared by in situ polymerization via the two-stage melt polycondensation procedure. BC was used as a filler for the PBSu to improve its mechanical properties, thermal transitions, and biodegradability. The structure of the synthesized poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Transmission electron microscopy (TEM) revealed that biochar is dispersed on a nanoscale in the PBSu matrix. Thus, our work confirmed that biochar can act as an effective reinforcing [ 29 , 30 ] and crystallization agent [ 29 , 30 ]. In addition to the mechanical properties, the thermal stability of a polymer is very important for processing and applications.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Transmission electron microscopy (TEM) revealed that biochar is dispersed on a nanoscale in the PBSu matrix. Thus, our work confirmed that biochar can act as an effective reinforcing [ 29 , 30 ] and crystallization agent [ 29 , 30 ]. In addition to the mechanical properties, the thermal stability of a polymer is very important for processing and applications.…”
Section: Introductionsupporting
confidence: 78%
“…As determined in our previous work by TEM, biochar is dispersed in the PBSu matrix at a nanoscale, acting as an effective reinforcing agent [ 29 , 30 ], whereby it improves the mechanical properties. This dispersion could be a result of the evolved interactions taking place between biochar and the PBSu matrix, which could also affect the thermal decomposition of nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is clear that some aggregates are formed in the nanocomposites containing 2.5 and 5 wt.% biochar, but even in these samples the sizes of aggregates are not larger than 1 μm. From these micrographs, we can conclude that the in situ technique that was used for the preparation of nanocomposites is appropriate to break down the initial large particles of biochar (10–15 μm) at nanosized level [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the main challenges in the use of PBSu biochar composites is the optimization of their properties and performance This can be achieved through the careful selection of the biochar and PBSu materials and the processing conditions used to produce the composite. From our previous work it was found that the fine dispersion of biochar in PBSu matrix improves the tensile and impact strengths [ 15 ]. Further research and development in this area could lead to the creation of new and improved PBSu biochar composites with enhanced capabilities and wider applications.…”
Section: Introductionmentioning
confidence: 99%